Reinforcing effectiveness of midazolam, ethanol, and sucrose: behavioral economic comparison of a mixture relative to its component solutions. Issue 5 (August 2017) - Townsend, E. Andrew; Platt, Donna M.; Rowlett, James K.; Roma, Peter G.; Freeman, Kevin B.
Abstract : Benzodiazepines (BZs) are relatively safe when administered alone. However, these drugs can produce severe side effects when coadministered with ethanol. Despite these adverse consequences, rates of concurrent BZ and ethanol misuse are increasing, and it is unclear whether this behavior is maintained by an enhanced reinforcing effect of the mixture. To address this issue, the current study compared the reinforcing effectiveness of sucrose solutions mixed with midazolam, ethanol, or both. Eight male rats were trained to orally self-administer solutions of either sucrose (S), sucrose+midazolam (SM), sucrose+ethanol (SE), or sucrose+midazolam+ethanol (SME). The response requirement was increased between sessions until the number of reinforcers earned was zero and the relationship between response requirement and reinforcers earned was analyzed using the exponential model of demand. Although baseline intake was similar across drug conditions, consumption of SM was least affected by increases in cost, indicating that it possessed the highest reinforcing effectiveness (i.e. least elastic). The reinforcing effectiveness of S, SE, and SME did not differ significantly. The finding that the reinforcing effectiveness of the SME was less than that of SM does not support the supposition that BZ and ethanol coadministration is maintained by a higher reinforcing effectiveness of the mixture.